Research, Ethics and Indigenous Peoples: An Australian Indigenous perspective on three threshold considerations for respectful engagement. (December 2016) - Kwaymullina, Ambelin
Indigenous peoples have long critiqued the harmful effects of Eurocentric research processes upon Indigenous cultures and communities. This paper—which is grounded in the author's knowledge and experience as an Aboriginal Australian academic—examines three threshold considerations relevant to non-Indigenous scholars who seek to enter into respectful research relationships with Indigenous peoples or knowledges. The first is the question of whether the research should be conducted at all. The second is positionality and how this affects research. The third is the need for scholars to comprehensively inform themselves about ethical research principles, including in relation to free, prior and informed consent, and Indigenous cultural and intellectual property.